Static and Kinetic Friction From Nanoscale Slip—A Multiscale Approach Using a 2D Binary Hierarchy of Nodes - Streator, Jeffrey L. (Frontiers in Materials, 2022)
A local, elastic deformation model is combined with a dynamic simulation to investigate nanoscale slip between a rigid, curved pin and an elastic slab, and its influence on static and kinetic friction. The elastic deformation model utilizes a novel multiscale grid based on a binary hierarchy. To maximize accuracy, bi-quadratic functions are introduced to interpolate the stresses on the boundaries of the nodal elements. The onset of slip is based on a maximum allowable nodal stress to nodal pressure ratio. A nanoscale friction function is developed by translating the pin quasistatically across the slab. The effect of the nanoscale friction profile on a dynamic system is investigated by integrating the equations of motions governing the pin as it is pulled by a stage via a coupling spring. A direct connection is found between the nanoscale slip characteristics and macroscopically observed static and kinetic coefficients of friction.